2002
DOI: 10.1007/s00467-001-0782-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoptosis of peripheral blood lymphocytes in children with nephrotic syndrome

Abstract: Nephrotic syndrome is accompanied by and probably related to abnormal T-lymphocyte function. Decreased stimulation of survival factors and increased levels of "dead signals" may lead to the malfunction of many cells, including lymphocytes. In our study, we investigated the process of apoptosis within T cells in children with a first attack of nephrotic syndrome (NS). We found that the number of apoptotic T cells is greater in these patients than in both children in remission from NS and in controls. The percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
1
24
0
3
Order By: Relevance
“…One recent study suggested a role of apoptosis as explanation of abnormal function and number of lymphocytes; however, this cannot explain the divergent findings of specific subpopulations [28]. Furthermore the increased apoptotic rate was only present in relapse and not in remission and is therefore not able to explain all results.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…One recent study suggested a role of apoptosis as explanation of abnormal function and number of lymphocytes; however, this cannot explain the divergent findings of specific subpopulations [28]. Furthermore the increased apoptotic rate was only present in relapse and not in remission and is therefore not able to explain all results.…”
Section: Discussionmentioning
confidence: 48%
“…The positive correlation of CD8+ and IgM for the first time links studies of the cellular and humoral immune system in SSNS and indicates a potential role in the suggested defective switch from IgM to IgG synthesis in SSNS, but this has not been proven yet and warrants further study. In general, further study especially of CD8 lymphocyte function is clearly needed, especially since recent data demonstrate that this subset is involved in cytokine production in SSNS [22]. By this alone [23], this subset may be a key player in the pathogenesis of this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This was in contrast to the published study by Gulati et al (4), in which patients with late steroid + expression in FSGS rituximab responders compared with those in both nonresponders and controls, and it was associated with significantly reduced mitogen-stimulated CD3 production of IFN-g and IL-2. The baseline immunologic signature in our FSGS rituximab responders was also significantly different from that in patients with MCNS in relapse as shown in Table 3, indicating that the immunologic basis underlying the nephrotic syndrome is likely to be distinct in this group of FSGS rituximab responders compared with those in patients with MCNS, in whom increased mitogen-stimulated lymphocyte production of IL-2 and IFN-g has been shown (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, few studies supported a Th1-dominant response in MCD. For example, Zachwieja et al [26] described an increased expression of IL-2, another Th1 cytokine, in their flow cytometry experiments. Although our study also showed a moderate expression of Th1 cytokine IFN-γ in MCD, its expression level was significantly lower than that of IL-4.…”
Section: Discussionmentioning
confidence: 99%